Medical Imaging 2020: Computer-Aided Diagnosis 2020
DOI: 10.1117/12.2549923
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a deep learning malignancy model from full-field digital mammography to digital breast tomosynthesis

Abstract: Mammography-based screening has helped reduce the breast cancer mortality rate, but has also been associated with potential harms due to low specificity, leading to unnecessary exams or procedures, and low sensitivity. Digital breast tomosynthesis (DBT) improves on conventional mammography by increasing both sensitivity and specificity and is becoming common in clinical settings. However, deep learning (DL) models have been developed mainly on conventional 2D full-field digital mammography (FFDM) or scanned fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The authors [ 14 ] used a deep learning model that has been trained on FFDM images and then modify it to operate with DBT images. These images were divided into four categories according to their FFDM and DBT content.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors [ 14 ] used a deep learning model that has been trained on FFDM images and then modify it to operate with DBT images. These images were divided into four categories according to their FFDM and DBT content.…”
Section: Related Workmentioning
confidence: 99%
“…This problem can be somewhat resolved if you think of a tomographic image and perform any analysis. Many studies have shown that using a 2D radiomics technique can get comparable results to radiomic analysis [ 12 ] of a straightforward mathematical formulation for radiomic properties [ 13 , 14 ]. Due to the fact that the information is being supplemented in a 2D manner, it is possible to create robust diagnostic classifiers.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we compare SpotTUnet with the best unlearnable layer choice strategies within the supervised DA setup and show it to be a reliable tool for domain shift analysis. While authors of [13] demonstrate SpotTune to perform worse than histogram matching preprocessing in the medical image classification task, we argue that histogram matching is a task-specific method and show its extremely poor segmentation quality in our task. Many approaches competitive to SpotTune have been developed recently, but their focus is more narrow: obtaining the best score on the Target domain rather than analyzing domain shift properties.…”
Section: Related Workmentioning
confidence: 64%
“…Supervised DA methods On the rest of the 25 testing pairs, we compare 4 methods: fine-tuning of the first network layers, fine-tuning of the whole network from [12], histogram matching from [13], and SpotTUnet. We load a baseline model pretrained on the corresponding Source domain and then fine-tune it via one of the methods or preprocess the Target data in case of histogram matching.…”
Section: Methodsmentioning
confidence: 99%
“…When compared to stacked CNN, the addition of residual blocks in the network increases representation power, leads to faster convergence, and lowers training errors [ 82 ]. A work by Singh et al [ 83 ] proposed a pre-trained model with FFDM images, which was utilized for DBT images. This study used two fine-tuning methods: (1) fine-tuning the last two layers and (2) fine-tuning only the optimal layers.…”
Section: Breast-cancer-diagnosis Methods Based On Deep Learningmentioning
confidence: 99%